THE USE OF AN IMPORTED NdFeB MAGNET IN DESIGNING AND FABRICATING AXIAL FlUX PERMANET MAGNET GENERATOR - Ginting, Masno; Sebayang, Perdamean; Siregar, Elfrida (Teknologi Indonesia, 2015)
Axial flux generator that consists of two rotors and one stator has been engineered. The rotor consists of eightimported NdFeB permanent magnets with 6 x 4 x 0.7 cm dimension and remanant (Br) 1.1 Tesla. The stator with 300 mm diameter consists of a spoils with 80 mm diameter with 400 coils, and the diameter of copper wire is 0.5mm, while the number of the spoil is varied. In this paper, the design and analysis for generator model has been done using 3DS MAX 2014 and Microsoft Visual Basic 2010 Express software, so that the right number of spoils in producing the optimal out put voltage (Erms) is obtained. From the experiment and simulation of axial flux permanent magnet (AFPM) generator, it has been obtained that there is correlation between the rotational speed (Vr in rpm) and the frequency and the voltage (Erms), which are given by equations i.e. frequency = 0.0667 Vr - 0.0001 and Erms = 0.4027 Vr + 3.2619, repectively. Meanwhile, the relation of the rotational speed and the number of spoils (Ns) to the outout voltage (Erms) is given by Erms = 0.0695 Ns Vr.